Bureaucratic Innovation in Disaster Response: A Public Service Perspective - Hermansyah; Abd Haris; Muhammad Yahya; Tawakkal Baharuddin (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
The urgency of this research lies in the increasing frequency and complexity of disasters in South Sulawesi, which demand that regional bureaucracies be able to innovate adaptively. This study aims to analyze the forms and characteristics of public service innovation, the factors influencing the bureaucracy’s role in accelerating disaster response, and the challenges of its implementation. The method used is a qualitative approach involving in-depth interviews, field observations, and documentation to understand bureaucratic innovation practices in crises comprehensively. Data analysis was conducted using NVivo 12 Plus with systematic coding and source triangulation to ensure the credibility of the research findings. The main findings of the study indicate that public service innovations in disaster management in South Sulawesi emerged in the form of simplified procedures, the formation of cross-governmental organizations (OPD) teams, the use of digital technology, and strengthened collaboration with the community and non-governmental actors. These innovations have been shown to accelerate responses, improve service accuracy, and enhance the quality of public services for affected communities. However, the effectiveness of innovation is strongly influenced by institutional capacity, bureaucratic leadership, cross-sector coordination, and regulatory and resource support. The study also found that public service innovations tend to be reactive and temporary, requiring institutionalization and policy strengthening to ensure sustainability over the long-term disaster cycle.